PROFIL JENIS PERTANYAAN SISWA SMA BERDASARKAN TAKSONOMI BLOOM REVISI - Lissa Lissa (Edu Sains: Jurnal Pendidikan Sains & Matematika, 2017)
The purpose of the research is to represent the classification of the students' questions based on revision of Bloom taxonomy about ecosystem material in SMAN 1 Sindang Indramayu. Subject of the research are the   students of X MIA 4 SMA Negeri 1 Sindang Indramayu. Based on the result of analysis through Revision of Bloom Taxonomy, these questions classified into cognitive aspect of C1 (remembering) 25%, C2 (Understanding) 43,75%, C3 (Doing) 12,5%, C4 (Analyzing) 6,25%, C5 (Evaluating) 12,5% and C6 (Creating) 0%. While from knowledge aspect, factual was 12,5%, conceptual 37,5%, procedural 12,5%, and cognitive 37,5%. The result of questionnaire and interview shows that the students are motivated to ask questions because the material is exciting . Besides, the students find that it is difficult to understand the concept of material. By using revision of Bloom taxonomy, it will be easier for the teacher to classify or evaluate the students' questions or difficulties about the material.